Sistem Pengelolaan Pelayanan Desa Berbasis Website “SIRABAT” Ragung Hebat Dalam Rangka Penguatan Digitalisasi - Ainul Fajar; Desiyanto, Jatim; Rohisotul Laily (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
Digitalization of services inscope of the Village government is indeed very necessary to improve the modernization aspect. so that there is a need for a platform that can facilitate the community in completing their personal needs. The purpose of this research is to find out the realization of a Website-based Village service system.realization of a Website-based Village service system. 2), Knowing the effectiveness of the Website-based Village service system This research method uses descriptive qualitative, the results showed that, 1. qualitative, the results showed that, 1). web-based digital services are very helpful for Village officials and the community. web-based digital services are very helpful for Village officials and the local community, seen from several supporting aspects including; 1).from several supporting aspects including; 1 the display of the Village home menu of the Website Sirabat.com Website home menu display is very easy to read and understand by the admin; 2) contact service is clearly displayed, making it easier for the admin to read and understand. services are clearly displayed, making it easier for users to carry out the process of sending messages to the admin (Village Website manager Sirabat.com). sending messages to the admin (Village Website manager); 3). Website pages that are responsive Website page and can be accessed from any device makes it easier for the admin to manage and update the Website content, including manage and update the contents of the Website including, information dissemination, services, activities, etc. 2). The existence of digital-based Village services is more The existence of digital-based Village services makes it easier for people who have an interest in administrative matters by by pressing the service menu located on the Sirabat.com start menu, all interests will be responded to by the admin and visitors and newcomers. interests will be responded to by the admin and visitors and newcomers can easily access various information and services about the Profil of the Village. visitors and newcomers can easily access various information and services about the Village Profil, With the existence of this Village Profil.